Design of manufacturing simulations of a flatplate pulsating heat pipe - Pontecorvo, Matteo (Vysoké učení technické v Brně, Fakulta strojního inženýrství, 2019)
Currently, a research team in the University of Brighton, in collaboration with the European Space Agency (ESA), is developing a pulsating heat pipe that will eventually be launched and tested in space, with the International Space Station (ISS) as destination, for research into passive thermal devices and their behaviour in a vacuum. The approved pulsating heat pipe design incorporates one titanium plate, which is classified as a metal, and one aluminum-oxide sapphire plate that is classified as a ceramic. At the moment, the team is faced with the challenge of bonding the two plates together since, using convectional manufacturing methods, the parts fail due to the high level of induced stress. A research into manufacturing processes to bond together titanium and sapphire is essential to ensure that the final device will operate for several weeks (maybe even months) without leaking and the need for maintenance. The project explores potential manufacturing processes aimed to bond together these materials and subsequently propose a solution. Furthermore, static and thermal analyses are carried out with the aid of SolidWorks to exploit potential points of failure due to stress concentrations induced by cooling after bonding. The results indicate that both titanium and sapphire are capable of sustaining the induced stresses but, due to the complex geometry of the pulsating heat pipe at the contact surface, the bonding agent is likely to fail due to the induced stresses.
Keywords: Pulsating heat pipe; induced stress; titanium; sapphire; active soldering; bonding agent; static and thermal analyses